The Determination of Partition Coefficient of 6-Mercaptopurine Derivatives by Thin Layer Chromatography - Andrzej Czyrski; Bartłomiej Kupczyk (Journal of Chemistry)
Mercaptopurine and its derivatives are used in the treatment of leukemia. To estimate their lipophilicity, a simple and novel thin layer chromatography method was developed. The mobile phase was the mixture of acetonitrile and water. The acetonitrile content varied by 5% from 50% to 80%. The linear relationship between log𝑃 and 𝑅𝑚0 for substances with known lipophilicity was found. The lipophilicity of purine derivatives was worked out from the calibration curve. The most lipohilic compound was methylazathioprine (0.64).